Fine Tailings Heap High Levels of Radiation Seepage Drainage Wells Application. (May 2019) - Zeng, Kaihua; Dai, Hongtao; Yao, Hui
Abstract: Jiangxi Xingan Xinheng mining tailings, the tailings discharge chute fracture accident, backfilling materials caused by leakage. After emergency measures for drainage tunnel mouth sealed, to make the library lost only drainage channels, the backfilling is fine drainage is poor, saturation line rising, pose a safety hazard. In this paper, Xinheng mining tailings as an example, put forward the suitable level of tailings backfilling fine particle size, small permeability coefficient e radiation well engineering measures and construction technology, let the radiation well drainage and horizontal tube drainage measures etc, for drainage effect comparison and analysis, the results show that, using the radiation well drainage measures more outstanding. Short construction time limit for a project, drainage effect is good, can provide the basis for other similar tailings e measures adopted and the reference.